Alasan Konsumen Merasa Jijik Terhadap Produk Makanan Tertentu - L. Retno Adriani (Bina Ekonomi, 2001)
Disgust is approached as a food-related emotion and defined as revulsion at the prospect of oral incorporation of offensive objects. These objects have contamination properties; if they even briefly contact an otherwise acceptable food, they tend to render it inedible. Some customers considered some factors as disgusting. They are the nature of the objects of disgust and they are virtually all of animal origin, the meaning of oral incorporation, the `belief ‘ that people take on the properties of the foods they eat, the nature of the contamination response and its relation to the laws of sympathetic magic (similarity and contagion), and the idea that faeces as the universal and the first disgust object. Disgust is developed after eight years of life. There are a number of life situations in which the weakening of disgusts regularly occurs.